Correlation between PSA kinetics and PSMA‐PET in prostate cancer restaging: A meta‐analysis. (11th January 2019) - Pereira Mestre, Ricardo; Treglia, Giorgio; Ferrari, Matteo; Pascale, Mariarosa; Mazzara, Calogero; Azinwi, Ngwa Che; Llado', Anna; Stathis, Anastasios; Giovanella, Luca; Roggero, Enrico
Abstract: Background: Serum prostate‐specific antigen (PSA) may predict the risk of positive positron emission tomography/computed tomography with radiolabelled prostate‐specific membrane antigen (PSMA‐PET/CT) in patients with biochemical recurrent prostate cancer (BRPCa). However, to date, there are no clear data regarding the correlation between PSA kinetics and PSMA‐PET findings. We performed a systematic review and meta‐analysis to provide evidence‐based data in this setting. Methods: A comprehensive literature search of studies published through October 2018 in PubMed/MEDLINE, EMBASE and Cochrane library databases was performed. A meta‐analysis to establish the detection rate (DR) of PSMA‐PET using different cut‐off values of PSA doubling time (PSAdt) and a pooled analysis to establish whether shorter PSAdt may predict positive PSMA‐PET results was performed in patients with BRPCa. Results: Twelve articles were included in the systematic review, and eight articles (including about 1400 patients) were selected for the meta‐analysis. The pooled DR including 95% confidence intervals (95%CI) of PSMA‐PET in restaging prostate cancer (PCa) patients was 72% (95%CI:60%‐82%), increasing to 83% (95%CI:75%‐90%) when PSAdt was ≤6 months and decreasing to 60% (95%CI:37%‐80%) when PSAdt was >6 months, without a statistical significant difference. PSAdt ≤6 months may predict the positive result of PSMA‐PET (pooled odds ratio: 3.22; 95%CI:1.17‐8.88). Statistical heterogeneity among the included studies was found. Conclusions: PSA kinetics, and in particular shorter PSAdt, may be predictor of PSMA‐PET positivity in patients with BRPCa. Further larger studies in this setting are warranted.